Navigating the waters of academic publishing: Insights from a graduate writing course - Andres Marrugo (TESEA, Transactions on Energy Systems and Engineering Applications, 2023)
Editor-in-Chief Andres G. Marrugo discusses the complexities of academic publishing and the crucial role of broad-based learning in a graduate course on scientific writing. The editorial highlights the need for effective communication and comprehension of publishing models to prepare emerging researchers for the academic world.